2016
DOI: 10.1136/acupmed-2015-011036
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Laser Therapy for Chronic Non-Specific Low Back Pain: A Meta-Analysis of Randomised Controlled Trials

Abstract: ObjectiveThe efficacy of low-level laser treatment (LLLT) for chronic back pain remains controversial due to insufficient trial data. We aimed to conduct an updated review to determine if LLLT (including laser acupuncture) has specific benefits in chronic non-specific low back pain (CNLBP).MethodsElectronic databases were searched for randomised trials using sham controls and blinded assessment examining the intervention of LLLT in adults with CNLBP. Primary outcomes were pain and global assessment of improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 33 publications
1
69
0
3
Order By: Relevance
“…Low level laser devices with <1 W of power (e.g. Erchonia [McKinney, TX]) have been reported to significantly reduce chronic musculoskeletal pain [29] and may also prove useful in reducing acute perioperative pain and inflammation after superficial surgical procedures without producing side effects. Recent studies using even more powerful 'cold' lasers (which generate >20 W of power) suggest that this novel nonpharmacologic therapy may provide significant benefits for patients who currently require opioid-containing analgesics for managing their residual postsurgical pain, as well as other chronic pain conditions.…”
Section: Nonpharmacologic Pain Management Techniquesmentioning
confidence: 99%
“…Low level laser devices with <1 W of power (e.g. Erchonia [McKinney, TX]) have been reported to significantly reduce chronic musculoskeletal pain [29] and may also prove useful in reducing acute perioperative pain and inflammation after superficial surgical procedures without producing side effects. Recent studies using even more powerful 'cold' lasers (which generate >20 W of power) suggest that this novel nonpharmacologic therapy may provide significant benefits for patients who currently require opioid-containing analgesics for managing their residual postsurgical pain, as well as other chronic pain conditions.…”
Section: Nonpharmacologic Pain Management Techniquesmentioning
confidence: 99%
“…Previous studies suggested that LLLT was of limited benefit in patients with knee OA [9] and non-specific low back pain [10,13,14]. However, for patients with chronic joint and back pain not responding to non-opioid analgesics, HILT may represent a simple, non-invasive, and more cost-effective alternative to other non-invasive physiotherapy and electrostimulation modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Близкие данные были получены G. Glazov и соавт. [34], которые недавно представили метаанализ 15 РКИ (n=1039). В сравнении с ПЛ, применение НИЛИ обеспечило значимое отличие по уменьшению боли у пациентов с НБС: в среднем -1,40 см по 10-сантиметровой ВАШ (95% ДИ от -1,91 до -0,88).…”
Section: лазерная терапияunclassified